Analysis of the Guidance and Counseling Program in Elementary Schools and the Implications for Its Development and Solutions to Problems - Pu'ad Maulana; Neviyarni S; Yarmis Sukur; Rahmad Firmansyah; Thessia Permata Bunda (Manajia: Journal of Education and Management, 2024)
Primary education lays the foundation for students' social, family and academic environments, creating key moments in the development of a child's personality. Primary education also promotes positive morals and develops students' skills. They quickly develop developmental traits, needs and functions. Activities that support learning in primary schools include creating a healthy learning environment. Teachers who have extensive subject matter knowledge to see and understand students should contribute to creating a healthy learning environment. The teacher in question is also called a guidance and counseling teacher, or school counselor. School counselors and mentors are essential as they help students grow throughout their lives.